b-Chromatic number of Some Splitting Graphs - Arockiaraj, S.; Premalatha, V. (Journal of Informatics and Mathematical Sciences, 2015)
A b-colouring of a graph G is a proper vertex colouring of G such that each colour class contains a vertex that has atleast one neighbour in every other colour class and b-chromatic number of a graph G is the largest integer φ(G) for which G has a b-colouring with φ(G) colours. In this paper, we have obtained the b-chromatic number of the splitting graphs of path P_n, cycle C_n, star K_1,n, fan graph F_n, triangular snake T_n, the H-graph H_n, the corona graph P_n° K_1 and C_n° K_1.